Decoding information literacy ways of thinking in student learning: Influencing pedagogic methods - Mohamed, S. (South African Journal of Higher Education, 2020)
University students often experience hidden challenges in various courses across all levels of their academic careers. These difficulties often serve to deter student learning and academic progress which may end in high student failure rates. In some instances, this may be attributed to tacit assumptions that academic teachers make about their learners when preparing lesson plans, course content and learning assessments. It is often mistakenly assumed that students already possess the necessary information literacy ways of thinking to overcome bottlenecks within their respective disciplines. To this end, the Teaching and Learning Librarian at the University of the Western Cape (UWC) Library, collaborated with an academic teacher to decode specific disciplinary difficulties and to subsequently enhance the required information literacy knowledge practices in student learning. Using a qualitative research approach, this study reports on how an Economics and Management Science (EMS) lecturer and the librarian used the Decoding the Disciplines Paradigm (DtD) to identify and deconstruct troublesome concepts in the Business and Finance module. The DtD model provides a clearly delineated, seven-step process for identifying and analysing disciplinary challenges and provides guidelines for designing instructional, motivational and assessment strategies that support deep learning. Through the DtD Paradigm, the study identified specific information literacy proficiencies that should be developed or enhanced in student learning. Moreover, the article describes how, as one of the paradigm’s steps, pedagogic methods were transformed to develop information literacy ways of thinking.